Smart Mom, Adequate Nutrition, Healthy Kids - Dyah Woro Kartiko Kusumo Wardani; Baharika Suci Dwi Aningsih; Agustina Ida Pratiwi; Yetty Leoni Irawan; Lorensia Panselina Widowati; Dewi Novitasari Suhaid; Ni Nyoman Sri Artina Dewi; Margaretha Kusmiyanti; Mitra Kadarsih (LPPM UIKA Bogor, 2024)
Nutritional status is a measure of success in balancing the needs and fulfillment of children's nutrition, as indicated by the weight and height of children based on their age (Menteri Kesehatan Republik Indonesia, n.d.). Malnutrition is a serious condition in which a person's food intake does not match the nutrients they need. The 2018 Global Nutrition Report shows that Indonesia is among 17 countries that have three nutrition problems at once, called multiple nutrition problems. These include stunting, wasting, and overweight (obesity) (Global Nutrition Report, 2018). The most common nutritional problem in Indonesia is undernutrition. Children under five years old (0–5 years) are the age group that most often suffers from malnutrition or is one of the groups of people who are vulnerable to nutrition. The most decisive intervention in reducing the prevalence of stunting is in the first 1000 days of life of the child, or before the age of 2 years, because the growth of children aged 2-3 years has slowed down so that the process of catching up at this age has a smaller chance than the age of 6–24 months (Kusuma, 2013; TNP2K, 2017). The form of efforts made to prevent and overcome malnutrition in children is by providing counseling related to child growth and development and balanced nutrition in children to increase mothers' knowledge related to growth and development and balanced nutrition. This activity began by approaching partners to determine the date and process of activities planned for June 16, 2023, at the Teratai Putih Posyandu, Paseban Village, Senen District.